Polyamide resin for paper wet strength improvement - Андрієвська, Людмила Валентинівна; Глушкова, Тетяна Геннадіївна; Коптюх, Леонід Андрійович; Стретович, Світлана Сергіївна (Eastern-European Journal of Enterprise Technologies, 2016)
In order to enhance consumer properties of the tissue paper, effective chemicals, namely the epichlorohydrin-modified polyamide resin of different manufacturers, are selected for paper strength improvement in dry and wet conditions. The environmentally friendly Kymene 25X-Cel resin made in the USA is characterized by the highest efficiency. Also, the given resin appeared the most economic in production. Expenditure amounted to 2 kg per ton of paper. Fiber composition for paper production based on bleached sulphate softwood pulp – 40 %, bisulphate softwood pulp – 20 %, bleached sulphate hardwood pulp – 40 %, ground to 27–32°SR is developed. Such ratio of fiber semi-products provides the highest consumer properties of paper. It is found that the Kymene 25X-Cel resin should be added to the paper pulp after grinding of cellulose fibers and diluted with water prior to introduction. Under these conditions, the highest efficiency of the resin is achieved. Paper samples with different contents of the epichlorohydrin-modified polyamide Kymene 25X-Cel resin (0.2–0.8 % of absolutely dry fiber), which were compared with the paper sample made without the resin are made. It is determined that 0.6–0.8 % of absolutely dry fiber is an effective resin content in the paper composition. It allows achieving the necessary paper strength of 9.3–9.6 % for the developed fiber composition, which provides basic operational properties of finished products.